Guatemala por Fernando Sétimo: Crisis dinástica, juegos de lealtad y afirmación del poder local en una relación de fiestas - Sánchez Mora, Alexánder (Revista de historia., 2017)
The proclamation of Ferdinand VII in the city of Guatemala bequeathed, from the pen of Antonio Juarros, one of the most complete examples of the literary genre of the Baroque festivals. Guatemala por Fernando Sétimo el día 12 de diciembre de 1808, is both a synthesis of the complex political events that the Spanish empire faced as a result of the French invasion of the Iberian peninsula as a sample of the transformations experienced by the rhetoric of loyalty that had operated during the Baroque period both sides of the Atlantic.